The role of reverse genetics systems in studying viral hemorrhagic fevers - Ebihara, Hideki; Groseth, Allison; Neumann, Gabriele; Kawaoka, Yoshihiro; Feldmann, Heinz (Thrombosis and haemostasis, 2005)
Viral hemorrhagic fever (VHF) is an infectious syndrome in humans often associated with high fatality rates. For most VHFs there are no specific and effective therapies or vaccines available and, in general, there is a lack of knowledge regarding the biology and pathogenesis of the causative agents. Therefore, a more detailed understanding of the molecular basis of VHF pathogenesis, including the identification of viral virulence determinants and host interactions and responses, will be important to enhance our ability to control VHF infections. The recently developed "reverse genetics systems" for several VHF causing viruses have allowed the generation of infectious viruses from cloned cDNA and thus, the generation of virus mutants. Here we review the existing reverse genetics systems for VHF causing viruses and discuss their use in studying viral replication, pathogenesis, and the development of antivirals and vaccines.